A master class in brand planning : the timeless works of Stephen King - King, Stephen, 1931-2006.; Lannon, Judie; Baskin, Merry (Chichester, West Sussex, England ; Hoboken, NJ : John Wiley & Sons, 2007)
In 1988, on Stephen King's retirement JWT published 'The King Papers' a small collection of Stephen King's published writings spanning 1967-1985. They remain timelessly potentially valuable but are an almost unexploited gold mine. This book is comprised of a selection of 20-25 of Stephen King's most important articles, each one introduced by a known and respected practitioner who, in turn, describes the relevance of the particular original idea to the communications environment of today. The worth of this material is that, although the context in which the original papers were written is dif.
Part I. Planning: Role and structure -- Who do you think you are? -- How brands and the skills of branding have flowered -- The price of freedom is eternal vigilance -- The market's evolved, why hasn't the planning? -- Learning and improvement, not proof and magic solutions -- The media planner's revenge -- Part II. Planning: Craft skills -- A revolutionary challenge to conventional wisdom -- Four of the wisest principles you will ever read -- JWT's debt to Stephen King -- Short-term effects may be easier to measure but long-term effects are more important -- Part III. Market research -- A theory that built a company -- The great bridge builder: Searching for order out of chaos -- You can't make sense of facts until you've had an idea -- Measuring public opinion in an individualistic world -- The perfect role model for researchers today -- Part IV. Marketing[:]General -- Old brands never die. They just get sold for a huge profit -- The retail revolution gets underway -- A robust defence of what brand advertising is for -- The train to Strawberry Hill (1744) -- A challenge to change behaviour.
Includes bibliographical references and index.
Print version record.
John Wiley and Sons
Keywords: Branding (Marketing) -- Management; New products; Brand name products; Advertising -- Management; Marketing research; x; Produits de marque; x; Marketing -- Recherche; BUSINESS & ECONOMICS -- Advertising & Promotion; Branding (Marketing) -- Management; Advertising -- Management; Brand name products; Marketing research; New products